2020
DOI: 10.31002/ijose.v4i1.2180
|View full text |Cite
|
Sign up to set email alerts
|

Record on Macroscopic Fungi at IPB University Campus Forest : Description and Potential Utilization

Abstract: <p>Fungi are ubiquitous and worldwide in distribution. It is estimated that tropical region such as Indonesia has high diversity of macro fungi. Studies on the diversity and potential utilization of macrofungi have gained significance during the recent years in Indonesia. However, information provide in the term of institutional area are still limited, and campus forest is no exception. The aim of this study was to collect information of mushroom diversity at IPB Unversity Campus Forest as inital step to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
1
12
0
8
Order By: Relevance
“…Lentinus is reported as a culinary-medicinal mushroom that possesses nutritious substances and biological activities (Lee et al, 2013;Mohammadnejad et al, 2019). Both Lentinus found in this study were different in colour and size with (Putra et al, 2019b;Putra, 2020a).…”
Section: Lentinus Sp1mentioning
confidence: 64%
See 2 more Smart Citations
“…Lentinus is reported as a culinary-medicinal mushroom that possesses nutritious substances and biological activities (Lee et al, 2013;Mohammadnejad et al, 2019). Both Lentinus found in this study were different in colour and size with (Putra et al, 2019b;Putra, 2020a).…”
Section: Lentinus Sp1mentioning
confidence: 64%
“…Members of the Agaricales are distributed worldwide with many representatives in tropical and temperate regions and a few species in arctic-alpine areas and deserts (Vellinga, 2004). In Indonesia, Putra et al, (2017;2018;2019a;2019b) and Putra (2020a) reported that Agaricales always found both in the natural and tourism areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamur merupakan organisme heterotrof yang bisa ditemukan di berbagai relung ekologi karena gaya hidupnya yang kosmopolitan (Putra et al, 2017) (Putra, Sitompul, and Chalisya 2018) (Putra et al, 2018) (Putra, Nasrullah, and Dinindaputri 2019) (Putra, 2020a) (Putra, Amelya, Nugraha, et al 2020) (Putra, 2020c) . Hingga saat ini telah diketahui sebanyak 70.000 -140.000 jamur yang telah didokumentasikan (Hawksworth 2001) (Blackwell 2011) dari total estimasi 1.500.000 jamur yang berada di alam (Blackwell 2011).…”
Section: A Latar Belakangunclassified
“…Macrofungi are known as cosmopolitan organism which are able to grow from natural to man-made areas (Putra et al, 2017;2018;2019a;2019b;Putra, 2020a;2020b;2020c;2020d). It is estimated that only around 140,000 mushroom species exist, with only about one-tenth which taxonomically identified (Hawksworth, 2001;Shelley & Geoffrey 2004).…”
Section: Introductionmentioning
confidence: 99%